Electronic spectra and ionization potentials of halogen oxides using the fock space coupled-cluster method - Vaval, N; Manohar, Prashant Uday; Pal, S (Collection of Czechoslovac Chemical Communications, 2005)
The ionization potentials and excitation energies of halogen monoxides and dihalogen oxides are studied using fully size-extensive Fock space version of multi-reference coupled-cluster theory. The low-lying excited states of ClO-, FO-, Cl2O and F2O are obtained along with the ionization spectra of Cl2O and F2O. The adiabatic electron affinity of ClO, FO and the vertical detachment energy of ClO- and FO- are also presented.

Constrained variational response to Fock-space multi-reference coupled-cluster theory: Some pilot applications - Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Molecular Structure-Theochem, 2006)
Fock space (FS) multi-reference (MR) coupled-cluster (CC) has been established to be state-of-the-art method for energies of open-shell radicals, ionized, electron attached states and excited states. Due to the multi-root nature of the method, the linear response of MRCC, however, is non-trivial. Constrained variation approach (CVA) makes it plausible to calculate response of the MRCC method efficiently. However, the approach is used for only one root of the problem at a time. In the present article, we make first implementation of the approach and present test results of dipole moments of small radicals. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: constrained variation; coupled-cluster; Dipole moment; Multi-reference; response

Constrained variational response to fock-space multi-reference coupled-cluster theory: formulation for excited-state electronic structure calculations and some pilot applications - Manohar, Prashant Uday; Pal, Sourav (Computational Methods in Science and Engineering Vol 1: Theory and Computation: Old Problems and New Challenges, 2007)
Fock-space (FS) multi-reference (MR) coupled-cluster (CC) method has emerged as compact tool to account for electronic structure of open-shell systems and molecules in low-lying excited states. Development of linear response (LR) has been one of the challenging problems in FSMRCC due to multiple-root nature of effective Hamiltonian. The recently developed constrained variational approach (CVA) has opened up a promising tool for efficient evaluation of analytic response properties. In this article, we present formulation of the method for excited state calculations. We discuss the decoupling of equations as a result of spin-adaptation and present some preliminary results for analytical dipole moments and polarizabilities of some molecules in low-lying triplet excited states.
International Conference on Computational Methods in Science and Engineering, Corfu, GREECE, SEP 25-30, 2007
Keywords: CVA; Dipole moment; excited states; FSMRCC; polarizability

Dipole moments and polarizabilities of some small radicals using constrained variational response to fock-space multi-reference coupled-cluster theory - Manohar, Prashant Uday; Pal, Sourav (Chemical Physics Letters, 2007)
In this Letter, we present dipole moments and polarizabilities of some open-shell doublet radicals, obtained analytically using constrained variational response to Fock-space (FS) multi-reference (MR) coupled cluster (CC) theory. These radicals can be treated as electron attached (EA) states of the corresponding closed-shell cations. Additionally, we also report analytical polarizabilities of some doublet radicals, which can be considered as ionized (IP) states of the corresponding anions. We compare our results with finite field FSMRCC response and the available benchmark results. (c) 2007 Elsevier B.V. All rights reserved.

First- and second-order electrical properties computed at the FSMRCCSD level for excited states of closed-shell molecules using the constrained-variational approach - Bag, Arijit; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2009)
Fock space multireference coupled-cluster (FSMRCC) method emerged as an efficient tool to describe the electronic structure of nearly degenerate cases. Development of linear response has been one of the challenging problems in FSMRCC due to the multiple-root nature of the effective Hamiltonian. A response from any of the roots would span the space for getting the properties. Hence, all roots perturbed by the external field would proliferate the excited states. We recently developed the FSMRCC method for the efficient evaluation of analytic response properties using a constrained variation approach. In this paper, we present analytic dipole moments and polarizabilities of H2O, O-3, and CH+ molecules in low-lying excited states along with brief discussion of singlet triplet decoupling of (1,1) sector of FSMRCC resulting from spin adaptation. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3167796]

On some aspects of fock-space multi-reference coupled-cluster singles and doubles energies and optical properties - Manohar, Prashant Uday; Shamasundar, K. R.; Bag, Arijit; Vaval, Nayana; Pal, Sourav (Recent progress in coupled cluster methods: theory and applications, 2010)

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Ground state of naphthyl cation: singlet or triplet? - Dutta, Achintya Kumar; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2014)
We present a benchmark theoretical investigation on the electronic structure and singlet- triplet(ST) gap of 1- and 2-naphthyl cations using the CCSD(T) method. Our calculations reveal that the ground states of both the naphthyl cations are singlet, contrary to the results obtained by DFT/B3LYP calculations reported in previous theoretical studies. However, the triplet states obtained in the two structural isomers of naphthyl cation are completely different. The triplet state in 1-naphthyl cation is (pi,sigma) type, whereas in 2-naphthyl cation it is (pi,sigma) type, The S-T gaps in naphthyl cations and the relative stability ordering of the singlet and the triplet states are highly sensitive to the basis set quality as well as level of correlation, and demand for inclusion of perturbative triples in the coupled-cluster ansatz. (c) 2014 AIP Publishing LLC.

Resolution of the identity and cholesky representation of EOM-MP2 approximation: implementation, accuracy and efficiency - Kumar, Dinesh; Dutta, Achintya Kumar; Manohar, Prashant Uday (Journal of Chemical Sciences, 2017)
We present a Resolution of Identity and Cholesky Decomposition Based Implementation of EOM-MP2 approximation. The RI and CD based EOM-MP2 shows significant speed-up and less storage requirement than the conventional canonical version and can be applied to very large systems. The new algorithm used for this implementation eliminates the most storage requiring four-index quantities resulting in the decrease of storage requirement, reduction in I/O penalties and improved parallel performance, at the expense of more floating point operations. Therefore, the speed-up compared to conventional EOM-MP2 method is more prominent in case of EA, EE and SF case where the storage bottleneck is significant than the EOM-IP-MP2 method, where the storage requirement is significantly less. However, the RI/CD based EOM-IP-MP2 can be coupled with frozen natural orbitals to gain further speed-up.
Keywords: CC; CD; Cholesky decomposition; EA; EE; electron attachment; electron correlation; EOM; equation-of-motion; excited state; ionization; IP; MP2; Resolution-of-identity; RI; SF; spinflip